The Contextual Effect of Posyandu on the Decision to Use Long Term Contraceptive in Tulungagung, East Java - Frafitasari, Dika Yanuar; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Family planning will help reduce population growth, fertility, improvement quality of life, women's health status, unwanted pregnancy, and abortion. The selection of the use of contraceptives needed leads to a contraceptive that has higher effectiveness, namely the long-term contraceptive method. This study aimed to analyze contextual effect of posyandu on the decision to use long term contraceptive in Tulungagung, East JavaSubjects and Method: This was a cross-sectional study conducted at 25 integrated health posts (posyandu) in Kauman health service, Tulungagung, East Java, in January 2019. A sample of 200 women of childbearing age was selected by stratified random sampling. The dependent variable was the use of long-term contraceptive method. The independent variables were age, education, knowledge, occupation, husband and family supports, women's perception, local culture, and posyandu. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression run on Stata 13.Results: The use of long-term contraceptive method increased with age ≥35 years (b= 1.68; 95% CI= 0.51 to 2.85; p= 0.005), education ≥Senior high school (b= 2.22; 95% CI= 0.97 to 3.46; p <0.001), high knowledge (b= 2.05; 95% CI= 0.75 to 3.35; p= 0.002), working outside the house (b= 1.66; 95% CI= 0.54 to 2.78; p= 0.004), strong husband and family support (b= 2.11; 95% CI= 0.87 to 3.34; p= 0.001), positive perception of long-term contraceptive method (b= 1.92; 95% CI= 0.75 to 3.08; p= 0.001), and supportive local culture (b= 1.10; CI 95%= -0.04 to 2.25; p= 0.009). Posyandu had strong contextual effect on the use of long-term contraceptive method with ICC= 26.70%.Conclusion: The use of long-term contraceptive method increases with age ≥35 years, education ≥Senior high school, high knowledge, working outside the house, strong husband and family support, positive perception of long-term contraceptive method, and supportive local culture. Posyandu has a strong contextual effect on the use of long-term contraceptive method.Keywords: long-term contraceptive, multilevel analysis.Correspondence: Dika Yanuar Frafitasari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: dikayanuar@gmail.com. Mobile: +6282145642707.Journal of Maternal and Child Health (2020), 5(1): 58-67https://doi.org/10.26911/thejmch.2020.05.01.07